Ajuste de histórico e previsão de produção de um reservatório heterogêneo pertencente à bacia potiguar - Martins , Beatriz Ferraz (Universidade Federal Rural do Semi-Árido, 2020)
This work consists of numerical simulation studies of oil reservoirs using a heterogeneous numerical model with characteristics of a medium oil field in the Potiguar Basin. The objective of this study was to carry out studies of generation of the dynamic model, adjustment of history and prediction of natural behavior, with water injection and polymer injection. From this it was possible to analyze improvements in the Recovery Factor of the produced oil and to evaluate the reduction of the mobility ratio of the fluids in place. To carry out this study, the numerical simulator of tNavigator reservoirs of the company Rock Flow Dinamics was used, using the inverted five-spot injection scheme for 21 years of simulation. The adopted methodology consisted of generating a dynamic model, from which the manual and automatic history adjustment was performed, after finding a satisfactory adjustment, a sensitivity analysis of the parameters of the studied model was performed. Then, behavior prediction simulations were performed and, for comparative purposes, in addition to these simulations, a prediction of oil volume using natural production was performed. The results indicated that the historical adjustment became satisfactory when using manual and automatic adjustment in sequence, thus optimizing the historical adjustment for the model, in addition to granting greater reliability to the forecast results. In addition, it was found that when compared to the injection of water alone, the injection of polymers for twenty years showed improvements in the Recovery Factor. According to the simulations planning, the best result of recovery factor was found in the simulation where there was continuous injection of water with polymer concentration of 200 ppm (D). For this case, there was an increase in the recovery factor of 21.29% when compared only to natural production and an increase of 8.38% when compared only with water injection. In general, the injection of polymers presented itself as a technically viable strategy for the field of study in question
Monografia
Keywords: Ajuste de histórico; Fator de recuperação; Injeção de polímeros; Simulação numérica; History adjustment; Recovery factor; Polymer injection; Numerical simulation; ENGENHARIAS::ENGENHARIA DE PETROLEO